Outcomes of Children With Cystic Fibrosis Admitted to PICUs*. Issue 10 (October 2020) - Smith, Michael A.; McGarry, Meghan E.; Ly, Ngoc P.; Zinter, Matt S.
Abstract : Objectives: Data on outcomes of children with cystic fibrosis admitted to PICUs are limited and outdated. Prior studies cite PICU mortality rates ranging from 37.5% to 100%. Given the advances made in cystic fibrosis care, we expect outcomes for these patients to have changed significantly since last studied. We provide an updated report on PICU mortality and the factors associated with death among critically ill children with cystic fibrosis. Design: Retrospective multicenter cohort analysis utilizing data from the Virtual Pediatric Systems database. Setting: Data were collected from 135 PICUs from January 1, 2009, to June 20, 2018. Patients: One-thousand six-hundred thirty-three children with cystic fibrosis accounting for 2, 893 PICU admissions were studied. Interventions: None. Measurements and Main Results: The primary outcome was mortality during PICU admission. Predictors included demographics, anthropometrics, diagnoses, clinical characteristics, and critical care interventions. Odds ratios of mortality were calculated in univariate and multivariable analyses to assess differences in mortality associated with predictor variables. Generalized estimating equation models were used to account for multiple admissions per patient. The overall PICU mortality rate was 6.6%. Factors associated with increased odds of mortality included hemoptysis/pulmonary hemorrhage, pneumothorax, gastrointestinal bleeding, bacterial/fungal infections, lower body mass index/malnutrition, and need for noninvasive or invasive respiratory support. Intubation/mechanical ventilation occurred in 26.4% of the 2, 893 admissions and was associated with a 19.1% mortality rate. Of the nonsurvivors, 20.7% died without receiving mechanical ventilation. Conclusions: The mortality rate during PICU admissions for patients with cystic fibrosis is lower than has been reported in prior studies, both in the overall cohort and in the subset requiring invasive mechanical ventilation. These data provide updated insight into the prognosis for cystic fibrosis patients requiring critical care. Abstract : Supplemental Digital Content is available in the text.